SELF-DISOCVERY AND RECONCILIATION IN THE NOVEL BELOVED BY TONI MORRISON - Yenti, Yenti (English Language, Linguistics, Literature, And Education Journal, 2025)
The objective of this research is to analyze the process of self-discovery and reconciliation experienced by the main character in the novel Beloved by Toni Morrison. This study aims to: (1) identify the types of identity found in the main character, (2) explore the interrelated processes of self-discovery, and (3) describe the aspects of reconciliation reflected in the novel. This research applies Erik Erikson’s identity theory, Charles Taylor’s self-discovery theory, and John Paul Lederach’s reconciliation theory. The method used is qualitative research with a descriptive approach, and the data were collected through documentation of character narratives and dialogues in the novel. The findings show that: (1) the most dominant type of identity is identity conflict, (2) the process of self-discovery involves four main elements acceptance of the past, the role of social relationships, awareness of autonomy, and symbolic influences, and (3) reconciliation includes past trauma, confrontation with the past, and recognition and acceptance. The result indicates that Beloved presents a deep psychological journey of identity formation and emotional healing through self-discovery and reconciliation.